Inter-Urban Variations in Attitudes Toward Community Mental Health and Correctional Facilites - Varrasso, Sandra (My University, 1989)
This research paper allows a comparison of attitudes towards two types of residential group homes in three cities. The main objective of the study is to examine variation in attitudes among the three cities, Toronto~ Ottawa and London. The second objective is to determine whether attitudes differ by type of facility, the mental health facility which serves psychiatric patients and the correctional facility which serves criminal offenders. Information for the study was obtained from a questionnaire conducted by the Canadian Training Institute (CTI) in 1983. Respondents were asked to indicate their attitudes towards the mental health and correctional facility in terms of their impacts on the neighbourhood and their desirability at different distances to home. Sample characteristics of the three cities were evaluated to test the effects of demographic variables on attitudes. The results show that attitudes vary by city with the London sample expressing the most supportive attitude and the Ottawa sample, the least supportive. The level of opposition to the correctional facility is much greater for all facility impacts, distance locations and for each of the three city samples, Toronto, Ottawa and London.
Keywords: inter-urban; community; mental health; correctional facilites